PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DI LINGKUNGAN PEMERINTAH KECAMATAN BATANGHARI LEKO KABUPATEN MUSI BANYUASIN - Z Zakiah; Marios Helly (JURNAL KOMPETITIF, 2016)
From the processing of the data obtained coefficients regression for Variable Leadership (X1) is 0,542, the coefficients regression for Work Motivation (X2) is 0,583, and the coefficients regression for Work Training is 0,255, while the constant value is -12.940, so the Multiple Regression Equation research are:Y = -12.940 + 0,542X1 +  0,583X2 +  0,255 X3Reseach explains that the Work Motivation is more influential on employee Performance at Batanghari Leko Distric in the Musi Banyuasin Goverment.  So the implementation is that the leader continually increase their leader and increase the work training not only from result and value. Key words : Leadership, Work Motivation, Work Training